Pengaruh Kualitas Aplikasi Tokopedia terhadap Kepuasan dan Minat Pembelian Ulang dengan Metode Webqual 4.0 - Yurindera, Novan (SAFE-Network, 2024)
The Covid-19 pandemic has had an impact on various sectors and lines of life, including the economy and business. On the one hand, the economy has weakened, but on the other hand, the economy has also improved, especially in the electronic commerce sector due to the imposition of mobility restrictions. Tokopedia's online shopping platform is the leader of the e-commerce or marketplace market in Indonesia in terms of the number of visits. This study aims to empirically examine the effect of usability, information quality and service interaction quality of Tokopedia application on satisfaction and repurchase intention using the WebQual 4.0 method. This analysis uses independent variables, namely usability, information quality and service interaction quality. While the dependent variable is satisfaction and repurchase intention. The research method used is associative. The population in this study were users of the Tokopedia application who had already made a purchase, with a sample of 200 respondents who filled out a questionnaire via google form. Statistical method using Structural Equation Modeling (SEM) using SmartPLS which consists of outer model analysis, inner model analysis and continued with hypothesis testing. The results showed that usability, information quality and service interaction quality of Tokopedia application have significant positive effect on satisfaction. Another result is that usability and information quality of the Tokopedia application have significant positive effect on repurchase intention. However, service interaction quality of Tokopedia application has no effect on repurchase intention.